"It's like a lifeboat": stakeholder perspectives of an intensive comprehensive aphasia program (ICAP)". Issue 3 (4th March 2022) - Babbitt, Edna M.; Worrall, Linda; Cherney, Leora R.
ABSTRACT: Background: Intensive comprehensive aphasia programs (ICAPs) have gained popularity in recent years. Outcomes from ICAPs have demonstrated measurable improvements for most who take part, but how do people with aphasia and their family members experience an ICAP? Aim: The aim of this paper was to explore, through qualitative interviews, the experiences of persons with aphasia and their family members who took part in an ICAP. Methods & Procedures: Twelve interviews were conducted with persons with aphasia and family members regarding their experiences with the ICAP that they had just completed. Nine persons with aphasia were interviewed with their family members and three chose to take part in the interview alone. The Framework Analysis method was used to identify themes from the transcribed interviews. Outcomes & Results: The interviewees discussed four themes related to treatment, psychosocial environments, physical environments, and outcomes. The interviewees remarked on the challenges that were provided by the treatment and how the treatment was different from previous treatment. Comments were made related to the relationships the participants and families developed within the context of the program. The physical environment allowed for relationships to develop. The interviewees discussed the physical and social environment as important additional factors that contribute to the overall therapeutic effect of the ICAP. Positive outcomes were noted in language skills and psychosocial contexts. Conclusions: Based on interviewees' descriptions of this one ICAP, the concept of a therapeutic milieu was developed to describe how the intersection of the treatment, psychosocial interactions, and physical setting related to outcomes. Interviewees described how the therapeutic milieu of the ICAP was interwoven with the intensive therapy to create a "package" of therapy that led to improved outcomes. Implications for non-ICAP clinical practice is that participants linked more intensive therapy and greater social interactions with better outcomes.